Construção de um gateway baseado na plataforma CORBA para inserção das redes inteligentes no contexto da NGN - Durães, Elisama Rocha de Carvalho (2009)
The introduction of Public Telephony Network in Next Generation networks demands the construction of protocol translators embedded in signaling gateways. This research cares about the Intelligent Network insertion in the Next Generation Network context, with special attention to construction of the signaling gateway. For the construction of this software was used the OMG gateway model, the Messaging service and Load Balancing service us the supporting to add QoS to the gateway architecture. The Asynchronous Method Handling is analyzed and suggested like another service to be included on the gateway to improve more scalability and throughput of messages changes in CORBA environment. The gateways run over three ORBs – CORBA for Java (JacOrb, ORBACUS, and Orbix) with purpose to implant all ORBs services available and to test the software.